2021
DOI: 10.1080/08998280.2021.1951071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atrial fibrillation on inflammatory bowel disease hospitalizations—a nationwide retrospective study

Abstract: Systemic inflammation seen in inflammatory bowel disease (IBD) may cause electrophysiological changes in the atria leading to atrial fibrillation (AF). We analyzed data from the National Inpatient Sample for 2018 to identify all adult hospitalizations with a primary diagnosis of IBD, which were further divided based on the presence or absence of AF. The primary outcome was inpatient mortality while the secondary outcomes included inpatient complications, mean length of stay, and mean total hospital charge. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Therefore, atrial fibrillation seems to be an independent predictive factor of mortality in hospitalized patients with IBD while patients with advanced age, coronary artery disease, and heart failure have worse outcomes [26]; however, it is not clear whether atrial fibrillation represents a cardiovascular marker of adverse prognosis in this setting or directly promotes the adverse events. In keeping with the aforementioned findings, Kichloo et al demonstrated that atrial fibrillation is associated with increased mortality in hospitalized patients with IBD [27]. This study showed that patients with IBD and atrial fibrillation were older, and had more comorbidities such as diabetes, hypertension, obesity, dyslipidemia, cardiovascular disease, heart failure, and COPD (Table 2).…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, atrial fibrillation seems to be an independent predictive factor of mortality in hospitalized patients with IBD while patients with advanced age, coronary artery disease, and heart failure have worse outcomes [26]; however, it is not clear whether atrial fibrillation represents a cardiovascular marker of adverse prognosis in this setting or directly promotes the adverse events. In keeping with the aforementioned findings, Kichloo et al demonstrated that atrial fibrillation is associated with increased mortality in hospitalized patients with IBD [27]. This study showed that patients with IBD and atrial fibrillation were older, and had more comorbidities such as diabetes, hypertension, obesity, dyslipidemia, cardiovascular disease, heart failure, and COPD (Table 2).…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationsupporting
confidence: 72%
“…In keeping with the aforementioned findings, Kichloo et al . demonstrated that atrial fibrillation is associated with increased mortality in hospitalized patients with IBD [27]. This study showed that patients with IBD and atrial fibrillation were older, and had more comorbidities such as diabetes, hypertension, obesity, dyslipidemia, cardiovascular disease, heart failure, and COPD (Table 2).…”
Section: Inflammatory Bowel Disease and Atrial Fibrillationmentioning
confidence: 80%
See 1 more Smart Citation
“…Patients with IBD have an abnormal immune response to microbial dysbiosis, leading to a sustained stimulated pro-inflammatory state, and pro-inflammatory Th1, Th17, and γδ T cells are often associated with increased inflammatory injury, while subsets of T cells can help or exacerbate ischemic brain injury 9 , 10 . In addition, inflammatory bowel disease increases patients' risk of atrial fibrillation 11 , predisposes patients to recurrent ischemic cerebrovascular events, and stroke survivors with inflammatory bowel disease are more likely to have a worse prognosis than those without inflammatory bowel disease 12 . In addition, one study used two-sample bidirectional Mendelian randomization (MR) to analyze the relationship between stroke and osteoarthritis (OA), a common general inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%